Analysis Of Student Errors In Solving Mathematics Olympiad Questions For Ambon Catholic Junior High School Students Based On Learning Style - R. H. Yanti Silitonga (Institute of Computer Science (IOCS), 2022)
Student achievement in the national science olympiad in mathematics needs to be improved. One way that can be done is to describe the types of student errors in solving math OSN problems. And the learning styles of students. The research subjects were representative students from Ambon Catholic Junior High School for the Mathematics OSN at the district/city level, totaling one person. Data collection techniques were carried out by giving tests in the form of descriptions, interviews, and learning style questionnaires. The results showed that students made errors based on Newman's analysis, namely, reading errors, understanding questions, and transforming errors once each, processing skills errors and writing errors in the final answer 4. The results of the learning style questionnaire, students have a visual learning style. Some recommendations based on the results of this study are teachers need to provide assistance to students by paying attention to student learning styles.